Evidence in favor of linkage to human chromosomal regions 18q, 5q and 13q for bicuspid aortic valve and associated cardiovascular malformations - Martin, Lisa J.; Ramachandran, Vijaya; Cripe, Linda H.; Hinton, Robert B.; Andelfinger, Gregor; Tabangin, Meredith; Shooner, Kerry; Keddache, Mehdi; Benson, D. Woodrow (Human genetics, 2007)
The aim of this study was to identify regions of the genome that harbor genes influencing inheritance of bicuspid aortic valve (BAV) and/or associated cardiovascular malformation (CVM). Aortic valve disease is an important clinical problem, which often results in valve replacement, the second most common cardiac surgery in the United States. In every age group, a majority of cases of valve disease involves a BAV. BAV is the most common CVM with a reported prevalence of 1-2%. Heritability studies indicate that BAV determination is almost entirely genetic. We used a family-based genome-wide linkage analysis with microsatellite markers. Parametric and nonparametric analyses were performed with the software GENEHUNTER and SOLAR (Sequential Oligogenic Linkage Analysis Routines). Thirty-eight families (353 subjects) with BAV and/or associated CVM were assessed. Each participant underwent a standardized echocardiographic examination. The highest LOD score, 3.8, occurred on chromosome 18q between markers D18S68 and D18S1161. Two other chromosomal regions, 5q15-21 (between D5S644 and D5S2027) and 13q33-qter (between D13S1265 and 13qter), exhibited suggestive evidence of linkage (LOD > 2.0). Further, two previously reported linkage peaks on 9q34 and 17q24 were replicated in family specific analyses. No significant X chromosome linkage peaks were identified. In this genome-wide scan we demonstrate for the first time, that BAV and/or associated CVM exhibit linkage to chromosomes 18q, 5q and 13q. These regions likely contain genes whose mutation results in BAV and/or associated CVM indicating their important role in valvulogenesis and cardiac development.